In vitro gender-dependent inhibition of porcine cytochrome p450 activity by selected flavonoids and phenolic acids - Ekstrand, Bo; Rasmussen, Martin Krøyer; Woll, Felicia; Zlabek, Vladimir; Zamaratskaia, Galia (BioMed research international, 2015)
We investigated gender-related differences in the ability of selected flavonoids and phenolic compounds to modify porcine hepatic CYP450-dependent activity. Using pools of microsomes from male and female pigs, the inhibition of the CYP families 1A, 2A, 2E1, and 3A was determined. The specific CYP activities were measured in the presence of the following selected compounds: rutin, myricetin, quercetin, isorhamnetin, p-coumaric acid, gallic acid, and caffeic acid. We determined that myricetin and isorhamnetin competitively inhibited porcine CYP1A activity in the microsomes from both male and female pigs but did not affect the CYP2A and CYP2E1. Additionally, isorhamnetin competitively inhibited CYP3A in both genders. Noncompetitive inhibition of CYP3A activity by myricetin was observed only in the microsomes from male pigs, whereas CYP3A in female pigs was not affected. Quercetin competitively inhibited CYP2E1 and CYP1A activity in the microsomes from male pigs and irreversibly CY3A in female pigs. No effect of quercetin on CYP2E1 was observed in the microsomes from female pigs. Neither phenolic acids nor rutin affected CYP450 activities. Taken together, our results suggest that the flavonoids myricetin, isorhamnetin, and quercetin may affect the activities of porcine CYP1A, CYP3A, and CYP2E1 in a gender-dependent manner.
Keywords: Cytochrome P-450 Enzyme Inhibitors; Swine; jaterní mikrozomy; pohlavní dimorfismus; Female; Cytochrome P-450 Enzyme System; Microsomes, Liver; Animals; prasata; inhibitory cytochromu P450; ženské pohlaví; mužské pohlaví; Male; Sex Characteristics; zvířata; systém (enzymů) cytochromů P-450